Os dramas cantados de Guaramiranga - Ceará: memória, identidade e convívio - Francisco Jose Costa Holanda (2014)
This work is the result of an ethnographic research carried out in the city of Guaramiranga Ceará, with the purpose of studying The Sung Dramas, a traditional expressive manifestation linked to the performing arts that has remained alive in the Baturité Mountain Range over the last hundred years. We have sought to understand how music and scene interact to compose the theatrical representation of drama professionals from Guaramiranga. We have also sought to identify musical aspects of dramas regarding the creation of scenes, and the representation of the characters. Propose a classification based on the constituent aspects of the several forms of dramas observed, and show how certain dramas are formed from the concepts idiosyncratically linked to each drama master. We have found out a lack of academic studies and publications on the subject of this Thesis, which confirms the development of this research. Among the few studies found on the sung dramas of Ceará, the one from Pontes (2011), related to the Dramas of Tianguá, and the one from Barroso (to be published), concerning the ones from the Eastern Coast, have provided the dialogues among those, and the Dramas from Guaramiranga, the reason why the fieldwork has become a fundamental resource for the firsthand knowledge of the manifestation studied. We have chosen the registration of melodies into musical scores as well as the description of the scenic unfolding, which will enable future generations to use and enjoy this knowledge as an important contribution for the dissemination and preservation of the memory of Sung Dramas from Guaramiranga.